Asesoría técnica y legal para el reconocimiento jurídico de las directivas de 15 barrios de la ciudad de Otavalo ante el Ministerio de Desarrollo Urbano y Vivienda "MIDUVI" - Flores, Alejandro. (2020)
From the coordination, the Law and Social Management Careers have resumed the activities aimed at the registration of the neighborhoods of the Canton of Otavalo, for this signed the neighborhood agreements prior request of each one of them with the intention to support the necessary steps within the process before the MIDUVI and the GAD of Otavalo, in this way activities are carried out that cause a high benefit to the neighborhoods and binding students and interns can fulfill their hours of connection with society. As measures are expected to continue with this project set for the year 2021.